Analisis Kemampuan Koneksi Matematis Mahasiswa pada Materi Program Linear - Zulhendri, Zulhendri; Musdi, Edwin; Arnawa, Made (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe the mathematical connection abilities of students who have high, medium and low categories of ability in completing linear programming material. This type of research uses descriptive research with a qualitative approach. The subjects of this study were Mathematics Education students of Pahlawan Tuanku Tambusai University in semester V of the 2022/2023 academic year. The research instrument consisted of a mathematical connection ability test and interview guidelines. The results of the study, students who have high category abilities are able to meet the mathematical connection ability indicators and can solve the problems given well. Furthermore, students who have moderate category abilities show a lack of understanding of the mathematical connection ability indicators, have not been able to have skills between concepts in mathematics, students who have moderate category abilities have difficulty in making mathematical models from the problems given. Students who have low ability categories, cannot meet the mathematical connection ability indicators, and cannot master concepts in mathematics, and also have difficulty in making mathematical models from the problems given. Conclusion, students with high ability can meet the indicators of mathematical connection ability and solve problems well, while students with medium and low ability have difficulty in understanding and comprehending mathematical concepts, as well as in creating mathematical models from the problems given. Keywords: Mathematical Connection Ability, Mathematical Ability, Linear Program